Ideology in the Translation of Legal Treaties - Almarri, Saqer Abdulla (2012)
A Master of Arts Thesis in Translation and Interpreting (English/Arabic/English) by Saqer Abdullah Almarri entitled, "Ideology in the Translation of Legal Treaties." Thesis advisor is Dr. Basil Hatim and was submitted in April 2012. Available are both hard and soft copies of the thesis.